Bibliometric Services: Challenges For Librarians In Academic Universities - Wan Abdul Rahman, Wan Bujang; Margaret, Simeng (2014)
Bibliometric services are seen as an opportunity as well as a challenge for librarians to offer unique services to its targeted institutions and thereby raise the importance of the libraries within the communities in the institution. These unique services are given to assist researchers and academics to determine the nature of influence and impact of their researches. Demands for bibliometric analyses have grown considerably in the universities and research institutes across the world. Thus, the librarians began to offer bibliometric services to cater their users’ needs. Introduction of the bibliometric services in academic and research institutions enhances research support and strengthens the library and its visibility to researchers. This results in outstanding impact on library services and strengthening smart partnership between librarians and research institutions. UNIMAS Strategic Planning has highlighted in their Strategic Review Initiatives (SRI) the importance of bibliometric services and the Centre for Academic Information Services to support and be responsible for the bibliometric services. This paper is to share and explore the involvement of the librarians in support of the University’s ranking, evaluation of the publications, the use of bibliometric quantitative indicators (impact factor, citations count, H-Index, academic ratio and 5 years publications progress) to meet the requirements of the Malaysia Research Assessment (MyRA) Instrument, that is to assess the research performance of research related activities in public universities. Among the research tools being used are Journal Citation Reports (JCR), SCOPUS and ISI WoS to identify the publications, citations and impact factor for UNIMAS. Findings show that librarians should make use of the experiences, competencies and expertise to provide and disseminate the usage of knowledge that are required of them in their new redefined role.